Genome-wide association analyses of ovarian cancer patients undergoing primary debulking surgery identify candidate genes for residual disease - Ramachandran, Dhanya; Tyrer, Jonathan P.; Kommoss, Stefan; DeFazio, Anna; Riggan, Marjorie J.; Webb, Penelope M.; Fasching, Peter; Lambrechts, Diether; García, María J.; Rodríguez-Antona, Cristina; Goodman, Marc T.; Modugno, Francesmary; et al. (npj Genomic Medicine, 2024)
Survival from ovarian cancer depends on the resection status after primary surgery. We performed genome-wide association analyses for resection status of 7705 ovarian cancer patients, including 4954 with high-grade serous carcinoma (HGSOC), to identify variants associated with residual disease. The most significant association with resection status was observed for rs72845444, upstream of MGMT, in HGSOC (p = 3.9 × 10−8). In gene-based analyses, PPP2R5C was the most strongly associated gene in HGSOC after stage adjustment. In an independent set of 378 ovarian tumours from the AGO-OVAR 11 study, variants near MGMT and PPP2R5C correlated with methylation and transcript levels, and PPP2R5C mRNA levels predicted progression-free survival in patients with residual disease. MGMT encodes a DNA repair enzyme, and PPP2R5C encodes the B56γ subunit of the PP2A tumour suppressor. Our results link heritable variation at these two loci with resection status in HGSOC.
CRIS-Team Scopus Importer:2024-06-14